Harmony of the Self: Sangeet and the Quest for Mokṣa in Indian Thought - Ahetasamuddin (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This essay looks at the deep connection between Indian philosophical traditions’ sangeet (music) and the search for moksha (liberation). It looks at how sound can be used to bring about spiritual awareness. The study looks at how music works as both an art form and a spiritual practice (sādhanā) based on metaphysical ideas. It does this by using Vedic, Upanisadic, Bhakti, Nāda Yoga, and Tantric models. It looks at how musical ideas have changed over time and how rāga and tāla are more than just beautiful sounds; they are also energy patterns that connect our minds with the rhythm of the universe. Anāhata nāda, or “unstruck sound,” is at the heart of this vision. Listening becomes a trip inside to find the Self. The ideas in this paper come from the writings of Indian mystics like Mīrābāī, Kabīr, and Tansen, as well as philosophical works like the Nāyasāstra, the Nāda-Bindu Upaniṣad, and the Bhagavad Gītā. They show how music connects the physical world with the spiritual world. In the end, sangeet is seen as an active spiritual practice that connects the self to the Absolute and shows moksha not as a faraway goal but as an echo within.